2022
DOI: 10.3390/molecules27238568
|View full text |Cite
|
Sign up to set email alerts
|

Geniposidic Acid from Eucommia ulmoides Oliver Staminate Flower Tea Mitigates Cellular Oxidative Stress via Activating AKT/NRF2 Signaling

Abstract: Eucommia ulmoides Oliver staminate flower (ESF) tea enjoys a good reputation in folk medicine and displays multiple bioactivities, such as antioxidant and antifatigue properties. However, the underlying biological mechanisms remain largely unknown. In this study, we aimed to investigate whether ESF tea can mitigate cellular oxidative stress. Crude ethyl alcohol extract and its three subfractions prepared by sequential extraction with chloroform, n-butyl alcohol and residual water were prepared from ESF tea. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“…It possesses multiple pharmacological activities, with main activity being anticancer. 61 A recent article reports its antiviral activity against white spot syndrome virus via reducing STAT (signal transducer and activator of transcription) gene expression, thereby reducing viral replication. 62 Compound 11 has been studied as tool molecule for white spot syndrome virus replication inhibition.…”
Section: Resultsmentioning
confidence: 99%
“…It possesses multiple pharmacological activities, with main activity being anticancer. 61 A recent article reports its antiviral activity against white spot syndrome virus via reducing STAT (signal transducer and activator of transcription) gene expression, thereby reducing viral replication. 62 Compound 11 has been studied as tool molecule for white spot syndrome virus replication inhibition.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have found that phosphorylation of Akt had the ability to reduce cellular apoptosis and ease neuroinflammation in diverse pathophysiological conditions [ 47 49 ]. On the other hand, Akt signaling has been reported to regulate the Nrf2 transcription factors, which aid in suppressing oxidative stress and negatively modulating the inflammatory response [ 27 29 , 50 ]. Numerous studies have indicated that Nrf2 contributed to modulating the functional phenotype of microglia and enhancing microglial phagocytosis in brain injury [ 26 , 51 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…Disruptions to the Akt signaling pathway are associated with multiple human diseases, such as cancer, cardiovascular disease, and neurological disorders [ 24 , 25 ]. And it’s reported that phosphorylated Akt could upregulate the expression of nuclear factor E2-related factor 2 (Nrf2), which was involved in antioxidant and cytoprotective functions, inhibition of inflammation, and modulation of microglial functional phenotype [ 26 29 ]. Given the close relationship between the aforementioned proteins and Nrf2’s pivotal regulatory function, it is plausible that Mas receptor activation could mediate hematoma clearance and neuroprotection partially via the Akt/Nrf2 pathway in ICH.…”
Section: Introductionmentioning
confidence: 99%
“…NRF2 is an important regulator of cellular oxidative status. As well as DNJ, various natural products have been found to stimulate the NRF2 antioxidative response, such as chlorogenic acid, geniposidic acid, and glucoraphanin [36][37][38], which were thought to be of value to health. HO-1 is a well-known downstream target of NRF2.…”
Section: Discussionmentioning
confidence: 99%